2018
DOI: 10.1038/s41598-018-27356-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on Burkholderia pseudomallei growth, proteomic changes, motility and resistance to stress environments

Abstract: Burkholderia pseudomallei is a flagellated, gram-negative environmental bacterium that causes melioidosis, a severe infectious disease of humans and animals in tropical areas. We hypothesised that B. pseudomallei may undergo phenotypic adaptation in response to an increase in growth temperature. We analysed the growth curves of B. pseudomallei strain 153 cultured in Luria–Bertani broth at five different temperatures (25 °C–42 °C) and compared the proteomes of bacteria cultured at 37 °C and 42 °C. B. pseudomall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 45 publications
3
22
0
Order By: Relevance
“…In B. seminalis TC3.4.2R3, the flagellin gene fliC was downregulated, while the flhD , flhC and fliL genes were upregulated at 37 °C, suggesting differential regulation of these genes. Similar results were found in B. pseudomallei strain 153: more motility was observed at 37 °C than at 25 °C and at 30 °C more so than at 42 °C, although fliC was downregulated (−2.60-fold) 40 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In B. seminalis TC3.4.2R3, the flagellin gene fliC was downregulated, while the flhD , flhC and fliL genes were upregulated at 37 °C, suggesting differential regulation of these genes. Similar results were found in B. pseudomallei strain 153: more motility was observed at 37 °C than at 25 °C and at 30 °C more so than at 42 °C, although fliC was downregulated (−2.60-fold) 40 .…”
Section: Discussionsupporting
confidence: 83%
“…Since cytochrome genes are induced, it is expected that a microaerobic environment is created because cytochromes have high affinity for oxygen, triggering oxygen depletion in Burkholderia 41 . For B. seminalis TC3.4.2R3 grown at 37 °C, genes encoding chaperons and heat-shock proteins, universal stress proteins and several genes involved in cellular detoxification were upregulated to protect and ensure cell survival, as also observed in B. pseudomallei strain 153 at increased temperature 40 .…”
Section: Discussionmentioning
confidence: 65%
“…Our recent study demonstrated that the human body temperature at 37°C facilitates a high growth rate, flagellin gene ( fliC ) expression and maximum motility functions in B . pseudomallei [ 30 ]. These mechanisms and the abundant flagella production may be a prerequisite for acute infection and bacterial dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we excluded rice fields with a history of extensive use of fertilizers or chemicals, but none of the fields were completely free of fertilizer use. Several reports have suggested that a wide range of environmental factors might influence the distribution of B. pseudomallei [49,50,51,52]. Only gross soil texture and altitude were measured in this study.…”
Section: Discussionmentioning
confidence: 99%